2019
DOI: 10.1002/wer.1154
|View full text |Cite
|
Sign up to set email alerts
|

Influence analysis of different design conditions on urban runoff and nonpoint source pollution

Abstract: Urban waterlogging and nonpoint source (NPS) pollution caused by urbanization have considerably increased, and their control effects are affected by many factors. This study established a distribution model to analyze the influences of different rainfall conditions and rain garden layouts on runoff output and NPS pollution. Simulation results showed that (a) the reduction rates of the runoff and pollution load decreased from 45% to 23% and from 57% to 23% with increasing rainfall duration (1-24 hr). The flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Changes in water quality in coastal areas are influenced by both natural and anthropogenic factors [72][73][74][75][76]. Pollutants in the marine environment are not only from sewage discharge but also from natural activities, whereby water bodies transport pollutants through inherent circulation processes [77,78], including rainfall, runoff [79], seawater intrusion, and tidal intrusion, ultimately merging into the ocean. Water quality pollution encompasses a broad spectrum of sources and complex causes, rendering accurate results challenging through mechanistic analysis.…”
Section: Utilization Of Machine Learning In Water Quality Predictionmentioning
confidence: 99%
“…Changes in water quality in coastal areas are influenced by both natural and anthropogenic factors [72][73][74][75][76]. Pollutants in the marine environment are not only from sewage discharge but also from natural activities, whereby water bodies transport pollutants through inherent circulation processes [77,78], including rainfall, runoff [79], seawater intrusion, and tidal intrusion, ultimately merging into the ocean. Water quality pollution encompasses a broad spectrum of sources and complex causes, rendering accurate results challenging through mechanistic analysis.…”
Section: Utilization Of Machine Learning In Water Quality Predictionmentioning
confidence: 99%
“…The study showed that the model did not predict water quality concentrations in the bioretention outflow well; however, pollutant concentration predictions emanating from the impervious area (bioretention influent) were well predicted. SWMM was also used to assess the impact of rainfall conditions and rain garden proportion on stormwater retention and water quality in Xi'an, China (Li, Ma, Ma, Li, & Zhang, 2019), and the impact of LID (vegetated swales and rain gardens) in Kuala Lumpur, Malaysia (Rezaei et al, 2019). Li et al (2019) found that rainfall intensity was the primary influencing factor for water quantity concerns while the rain garden proportion impacted water quality.…”
Section: Bioretentionmentioning
confidence: 99%
“…SWMM was also used to assess the impact of rainfall conditions and rain garden proportion on stormwater retention and water quality in Xi'an, China (Li, Ma, Ma, Li, & Zhang, 2019), and the impact of LID (vegetated swales and rain gardens) in Kuala Lumpur, Malaysia (Rezaei et al, 2019). Li et al (2019) found that rainfall intensity was the primary influencing factor for water quantity concerns while the rain garden proportion impacted water quality. Rezaei et al (2019) also saw a positive impact on water quality from the implementation of LID.…”
Section: Bioretentionmentioning
confidence: 99%